2009
DOI: 10.1113/expphysiol.2009.049668
|View full text |Cite
|
Sign up to set email alerts
|

Is there an interaction between PPARD T294C and PPARGC1A Gly482Ser polymorphisms and human endurance performance?

Abstract: Functional Gly482Ser (rs8192678) and T294C (rs2016520) polymorphisms in the peroxisome proliferator-activated receptor γ coactivator-1 (PPARGC1A) and peroxisome proliferatoractivated receptor δ (PPARD) genes, respectively, have been associated with mRNA and/or protein activity. The aim of this study was to determine their frequency distribution among 155 Israeli athletes (endurance athletes and sprinters) and 240 healthy control subjects. There were no differences between the endurance athletes, the sprinters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 34 publications
2
37
0
2
Order By: Relevance
“…Since aerobic capacity highly depends on the skeletal muscle mitochondrial function (7), it is reasonable that functional polymorphisms in the PPARGC1A gene (Gly482Ser) would have an effect on the level of aerobic fitness. Previous studies have demonstrated a lower frequency of the PPARGC1A Ser482 allele in top-level endurance athletes among Caucasians (8)(9)(10)(11). Additionally, the PPARGC1A Ser482 allele has been shown to be independently associated with a lower increase in individual aerobic fitness after nine months of lifestyle intervention (12).…”
Section: Introductionmentioning
confidence: 97%
“…Since aerobic capacity highly depends on the skeletal muscle mitochondrial function (7), it is reasonable that functional polymorphisms in the PPARGC1A gene (Gly482Ser) would have an effect on the level of aerobic fitness. Previous studies have demonstrated a lower frequency of the PPARGC1A Ser482 allele in top-level endurance athletes among Caucasians (8)(9)(10)(11). Additionally, the PPARGC1A Ser482 allele has been shown to be independently associated with a lower increase in individual aerobic fitness after nine months of lifestyle intervention (12).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies from our laboratory indicated that the R577X substitution in the ACTN3 gene (Eynon et al 2009e) and several variants in the PPARGC1A-NRF-TFAM pathway (Eynon et al 2009a;2009b;2009c;2009d;) are associated with elite athletic status. We also suggested that in general, endurance athletes have a polygenic profile that is more adjusted for mitochondrial biogenesis, as opposed to power athletes or non-athletic controls (Eynon et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…His personal best running times are reported in Table 1. We genotyped six genetic SNPs in the PPARGC1A-NRF-TFAM pathway genes, which are known to be associated with endurance exercise performance capacity: (Eynon et al 2009d;He et al 2008); (iii) NRF2 C/T (rs8031031) (Eynon et al 2009a); (iv) peroxisome proliferator-activated receptor alpha (PPARA) intron 7 G/C (rs4253778) (Ahmetov et al 2006;Eynon et al 2009b); (v) peroxisome proliferator-activated delta (PPARD) C294T (Eynon et al 2009c); (Skogsberg et al 2003); and (vi) PPARGC1A Gly482Ser (Eynon et al 2009c;Lucia et al 2005). We also studied the ACTN3 R577X polymorphism, which is known to be associated with power-oriented performance (Druzhevskaya et al 2008;Eynon et al 2009e;Niemi and Majamaa, 2005;Yang et al 2003).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…All PPARs are subject to transcriptional coactivation by peroxisome proliferator-activated receptor gamma coactivator1 (PGC-1α). The PPARGC1A Ser482Gly (Eynon et al, 2009a;Eynon et al, 2009b;Lucia et al, 2005) and the PPARA intron 7 G/C (Ahmetov et al, 2006) SNPs were shown to be associated with elite aerobic performance.…”
Section: Introductionmentioning
confidence: 99%